How to Answer Dworkin's Argument from Theoretical Disagreement Without Attributing Confusion or Disingenuity to Legal Officials. Issue 1 (12th February 2023) - Watson, Bill
Abstract: Ronald Dworkin's argument from theoretical disagreement remains a pressing challenge for legal positivists. In this paper, I show how positivists can answer Dworkin's argument without having to attribute confusion or disingenuity to legal officials. I propose that the argument rests on two errors. The first is to assume that positivism requires legal officials to converge on precise grounds of law when convergence on more general grounds will do. The second is to construe judicial speech too literally. If we pay attention to the pragmatics of judicial speech, we see that judges do not disagree over what the grounds of law are; they at most disagree over how courts should proceed when agreed-upon, though imprecise, grounds of law underdetermine what the content of the law directs in the case at hand.